A crítica sociopolítica de Marx à religião - Feijão, Felipe Augusto Ferreira (2024)
Karl Marx's thought is not specifically concerned with religion. Contrary to what common sense tends to disseminate about it as being contrary to religion, the author did not formulate any specific treatise in relation to it. Nor is there, in the non-systematized reflections of his thought on the religious topic, a theory about religion. We can, then, say that Marx does not have an anthropological concern, but a social one with religion. What is religion? It is a social phenomenon and as such what matters is its interference in the lives of individuals, that is, the consequences of religion in the social-political sphere, in community and collective life. If religion as a human creation, historically manifested in societies, can condition men to a situation of idolatry, fanaticism, obscurantism and blindness to their reality, it must be experienced privately in relation to the State. The essay On the Jewish Question, from 1843, a work by Marx, will help in understanding the analysis made about religion carried out in the social and political situation. In the aforementioned work, Marx critically dialogues with Bruno Bauer, who addresses the issue of political emancipation limited to the critique of religion. Bauer fails to see that, according to Marx, the problem is beyond, it is necessary to replace the criticism of the theological State, which Bauer does, with the criticism of the profane State, that is, political, which Bauer does not do. In addition to political emancipation, human emancipation is not a fundamentally religious problem, but above all a social one. Finally, we realize that Marxian thought, based on criticism of the State, Law and real politics, offers a great contribution to reflect on religion today.